Impact of Obstructive Sleep Apnea (OSA) in COVID-19 Survivors, Symptoms Changes Between 4-Months and 1 Year After the COVID-19 Infection - Labarca, Gonzalo; Henríquez-Beltrán, Mario; Lamperti, Liliana; Nova-Lamperti, Estefania; Sanhueza, Sergio; Cabrera, Camilo; Quiroga, Romina; Antilef, Barbara; Ormazábal, Valeska; Zúñiga, Felipe; Castillo, Daniela; Horta, Gloria; et al. (Frontiers in Medicine, 2022)
Objective: To determine the association between OSA with long-term symptoms and inflammatory cytokines, exploring the changes between four months and one year after the COVID-19 infection. Methods: We conducted an observational, prospective cohort study. We included patients ≥ 18 years old with confirmed diagnoses of COVID-19 between April to July 2020. All participants undergone to two different clinical visits: one at four months (Visit 1) and the other one year after SARS-CoV-2 infection (Visit 2). The following laboratory parameters were evaluated: Plasma glucose, total cholesterol, HDL, and triglycerides. Regarding the pulmonary function, spirometry, and a diffusion lung capacity were evaluated. In relation to Mental and neurocognitive evaluation, a SF-12, Beck depression and the Hospital- Anxiety depression questionnaires were included. The Montreal Cognitive assessment was performed in visit 2. The Inflammatory cytokines was measured by a flow cytometry. Regarding to sleep evaluation, participants completed Epworth Sleepiness Scale, Insomnia Severity index and STOP-BANG questionnaire. Additionally, the participants completed a home sleep apnea test and 7-day wrist actigraphy. p-values < 0.05 were considered statistically significant and Statistical analyses were performed using R software. Results: A total of 60 patients were included (visit 1), and 57 of them completed visit 2. The mean age was 46.4 years-old (SD ±13.1) and 53.3% were male. 30% of cases reported mild COVID-19 infection, 28.3% with moderate illness, and 41.6% with severe illness. Moreover, 56.6% of them were admitted to the ICU. Regarding to metabolic values, the OSA group, showed higher values of IR (27%), SBP 135.2 (±19.1), dyslipidemia (67.5%), total cholesterol 202.1 (±60.5), triglycerides 176.1 (±119.0) and HOMA-IR 9.0 (±18.8) in comparison of non-OSA group. One year after COVID-19 infection, in OSA patients the DLCO test remains abnormal, 25% OSA group and 3.6% in non OSA group (p=0.02). Finally, those participants with OSA who develop ARDS reported an adjusted OR 20.4 (95%-CI, 1.04-504) risk of neurocognitive impairment. Discussion: Among patients with previous COVID-19, OSA impact the development of incident glycemic, neurocognitive impairment, and abnormal functional pulmonary changes that persist up to one year since acute phase. Keywords: COVID-19, Obstructive Sleep Apnea, symptoms, Cytokines, neurocognitive impairment